THE TRAINING OF HIGHLY QUALIFIED INVESTIGATORS IS AN IMPORTANT FACTOR IN THE MECHANISM OF ADMINISTRATION OF JUSTICE - Sattorova Shokhsanamkhon Rafikovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article discusses and analyzes the issues of training highly qualified investigators as an important factor in the mechanism of administering justice.